2009
DOI: 10.4314/wajae.v12i1.45777
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility status of <i>Anopheles gambiae</i> s.l. (Diptera: Culicidae) from cabbage growing areas associated with pyrethroid and organophosphate use in Accra, Ghana

Abstract: Resistance in malaria vectors is likely to be caused by the massive use of insecticides in agriculture. Anopheles gambiae s.l. collected from breeding grounds in two cabbage growing areas within Accra were assessed for levels of resistance to 0.75% permethrin, 0.05% deltamethrin, 5% malathion and 4% DDT using standard WHO susceptibility test kits. Pyrethroid and organophosphate residue levels in soil and runoff water from these cabbage farms were determined and possible association between resistance and resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 10 publications
(6 reference statements)
6
8
0
Order By: Relevance
“…gambiae complex found in the study area. This finding is consistent with earlier studies in the grater Accra Region (Appawu, 2001;Midega, 2001;Adeniran, 2002;Sibomana, 2002;Otieno, 2004;Achonduh, 2005). The two molecular forms of An.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…gambiae complex found in the study area. This finding is consistent with earlier studies in the grater Accra Region (Appawu, 2001;Midega, 2001;Adeniran, 2002;Sibomana, 2002;Otieno, 2004;Achonduh, 2005). The two molecular forms of An.…”
Section: Discussionsupporting
confidence: 82%
“…gambiae s.l. to insecticides have been conducted in Ghana (Adasi, et al, 2000;Adeniran, 2002;Otieno, 2004;Yawson et al, 2004;Achonduh, 2005;Kahindi, 2005), it is still important to continue monitoring changing trends of resistance. The information provides a basis for ascertaining continued susceptibility to and efficacy of pyrethroids, and for vector insecticide resistance management.…”
Section: Introductionmentioning
confidence: 99%
“…which reported a higher knockdown and mortality rate of mosquito susceptibility test upon combinations of different concentration and different active ingredients of herbal mosquito coils. The study also agrees with other studies in the Greater Accra region which reported resistance to pyrethroid based vector control methods (Adeniran, 2002;Achonduh et al, 2008;Boakye et al, 2009). The reasons why An.…”
Section: Discussionsupporting
confidence: 82%
“…gambiae s.s. population in the area is consistent with studies by Achonduh et al (2008), Adeniran (2002) in the Accra metropolis and Diabate et al (2002) in Burkina Faso, where the kdr gene was found to be highly present in An. gambiae s.s. in their respective areas.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation